Гістологічні і гістохімічні особливості епітелію червоподібного відростка людини в першій половині грудного періоду - Таврог, Маріанна Львівна; Сирцов, Вадим Кирилович; Зідрашко, Галина Анатоліївна; Алієва, Олена Геннадіївна; Хитрик, Аліна Йосипівна; Таврог, М. Л.; Сырцов, В. К.; Зидрашко, Г. А.; Алиева, Е. Г.; Хитрик, А. И.; Tavrog, M. L.; Sirtzov, V. K.; et al. (Полтава : [б. в.], 2016)
Резюме. У першій половині грудного періоду (десяти діб – п’яти місяців) слизова оболонка червоподібного відростка людини представлена одношаровим однорядним стовпчастим мікроворсинчастим епітелієм на всьому протязі цього періоду. Упродовж досліджуваного періоду у апікальних частинах збільшується синтез ШІК-позитивних речовин. Серед клітин покривного епітелію і крипт слизової оболонки червоподібного відростка людини постійно виявляються малі лімфоцити, на поверхні яких виявлені рецептори до лектину арахісу PNA+, CD3+ – тобто за функціональними особливостями відносяться до популяції Т-хелперів, з позитивною експресією CD4+. Виявляються стовпчасті епітеліоцити з позитивною експресією маркера проліферації Кі-67+. Вони розміщені на дні крипт. Резюме. В первой половине грудного периода (десять суток – пять месяцев) слизистая оболочка червеобразного отростка человека представлена однослойным однорядным столбчатым микроворсинчатым эпителием на всем протяжении этого периода. В течение исследуемого периода в апикальных частях увеличивается синтез ШИК-положительных веществ. Среди клеток покровного эпителия и крипт слизистой оболочки червеобразного отростка человека постоянно выявляются малые лимфоциты, на поверхности которых обнаружены рецепторы к лектину арахиса PNA +, CD3 + – то есть по функциональным особенностям относятся к популяции Т-хелперов, с положительной экспрессией CD4 +. Выявляются столбчатые эпителиоциты с положительной экспрессией маркера пролиферации Ки-67 +. Они размещены на дне крипт. Abstract. The purpose of the reaserch: to determine the morpho-functional features of the epithelium of the human appendix in the late prenatal ontogenesis. Materials and methods: appendixes of human fetuses (26), which deaths from accidents and other diseases, excluding gastro tract, the immune system and hematopoiesis. Immunohistological studies with monoclonal antibodies were performed: 1) Mo a – Hu Ki – 67 Antigen, Clone MIB – 1; 2) Mo a – Hu CD20cy, Clone L26; 3) Mo a – Hu CD8, T – Cell, Clone C8 / 144B; 4) Rb a – Hu CD3, Clone SP7; 5) Mo a – Hu CD4 Ab – 8, Clone 4B12; 6) Mo a – Hu Caspase 3 Ab – 3, Clone 3CSP03 and visualization system UltraVision LP («Thermo Scientific LabVision», USA). In the first half of infancy period (ten dib- five months) mucosa appendix man presented row single layer columnar epithelium mikrovorsynchastym throughout this period. Prismatic epithelial cells retain the structure and polarity tektorialni properties. The large oval nucleus contains nucleoli 1-2 located in parts of the basal cells. The height of the cells by the end of this period increases.During the study period in the apical parts increases the synthesis of SHIK-positive substances. After processing amylase and sialidazoyu these substances can be classified as neutral proteoglycans and sialic acids. Similar hlyukozaminohlikany marked and as part of glycocalyx on the surface of epithelial-row single-layer columnar epithelium mikrovorsynchastoho appendix person. The bar extends glycocalyx on the surface of epithelial cells. There is growing contents of goblet cells in the epithelium covering part of the crypts and mucosa of the appendix man from the first to the fifth thoracic month period, they produce proteoglycans and sialic acid in a ratio of 2: 1. Among cell surface epithelium crypts and mucosa of the appendix human breast in the first half period of research are always small cells on the surface are found receptors for peanut lectin PNA +. A immunohistochemical positive expression of CD3 + – the functional features relating to population of T-helper cells with positive expression of CD4 + In the epithelium of the crypts of the mucous membrane of the appendix of children in the first half of infancy (the first – in the fifth month) are columnar epithelial cells with positive expression proliferation marker Ki-67.
Гистологические и гистохимические особенности эпителия червеобразного отростка человека в первой половине грудного периода
Complex histological, histochemical and immunohistochemical study of the human appendix in the first half of infancy period
Keywords: червоподібний відросток людини; епітелій; перша половина грудного періоду; червеобразный отросток человека; эпителий; первая половина грудного периода; epithelium; human appendix; first half of infancy period